Interannual dynamics of breeding bird assemblage within the republican natural monument «Dubrava» (Minsk) - Sakhvon, Vital V.; Dombrovski, Valery Ch. (Experimental Biology and Biotechnology, 2019)
In this paper the changes of composition and diversity of breeding bird assemblage within the republican natural monument «Dubrava» during last 27 years was analysed. Urban park «Dubrava» (24 ha) is situated in southwestern part of Minsk and is presented by the oldyear natural mixed oakspruce forest with some introduced exotic plants in tree stand.   The absolute bird census was carried in 1991, 2015–2018. Total 47 breeding bird species were registered (from 28 to 38 species in a single year), 21 of them nests regularly. Overall bird densities varied from 7.16 pairs/ha to 13.02 pairs/ha. Total 10 species (Fringilla coelebs, Erithacus rubecula, Turdus merula, T. philomelos, T. pilaris, Parus major, Sylvia atricapilla, Phylloscopus sibilatrix, Sturnus vulgaris and Cyanistes caeruleus) were shown to be the dominants in assemblage during these years. Since 1991 till now a significant increase in composition and species richness (the breeding was confirmed for 14 new species in last years) and overall breeding bird density was observed. The main factors explaining the dynamics of some assemblage characteristics such as synurbization of some bird species and change in habitat structure are discussed.
Keywords: urban bird assemblage; bird diversity; breeding bird density; park; city; synurbization